The impact of syndromic treatment of sexually transmitted diseases on genital shedding of HIV-1. - Wolday, D; Gebremariam, Z; Mohammed, Z; Dorigo-Zetsma, W; Meles, H; Messele, T; Geyid, A; Sanders, E; Maayan, S (2004)
OBJECTIVES: To examine the impact of sexually transmitted diseases (STD) syndromic treatment on genital shedding of HIV and the impact among women in whom STD treatment was not successful. DESIGN: Seventy-one HIV-infected women were included; 60 had symptomatic STD [72% with genital discharge syndrome (GDS) and 28% with genital ulcer syndrome (GUS)] and 11 controls did not have symptomatic STD. Cervical HIV load in 94% women was measured at baseline and after STD treatment. RESULTS: Cervical HIV load at entry was significantly higher in women with symptomatic STD than in controls [median, 3.15; interquartile range (IQR), 1.90-3.34 versus median, 1.90; IQR, 1.90-2.19 log10 RNA copies/swab, respectively; P = 0.024]. Women with STD were also more likely to have detectable cervical HIV RNA (68% versus 27%; P = 0.016). Cervical HIV load was significantly higher in women with GUS than in those with GDS (median 3.46; IQR, 2.84-4.18 versus median, 2.83; IQR, 1.90-3.31 log10 copies/swab; P = 0.019). There was no significant reduction in genital HIV shedding after syndromic treatment of GDS or GUS. However, significant decreases were limited to only those with clinical improvement (median, 2.91; IQR, 1.90-3.45 versus median, 2.25; IQR, 1.90-3.08 log10 RNA copies/swab, respectively; P = 0.006). GUS was significantly associated with treatment failure, independent of plasma HIV RNA load and CD4 T-cell count (odds ratio, 4.79; 95% confidence interval, 1.32-17.46). CONCLUSIONS: The fact that STD syndromic treatment impacts very little in reducing genital HIV shedding underscores the need for appropriate validation of STD syndromic diagnosis and management to control heterosexual transmission of HIV.